A comparative analysis in the macro and micro nutrient compositions of locally available polished rice (Oryza sativa L.) in Bangladesh - Islam, Md.Jahirul; Das, Jayasree; Absar, Nurul; Hasanuzzaman, Md. (International Journal of Biological Research, 2016)
Rice (Oryza sativa L.) is the most important food crop of the developing world and the staple food of more than half the global population. An investigation was carried out to identify chemical and minerals composition of twelve varieties of locally produced polished rice namely, Parija, Minikat, Sawrna, Jeerashile, Nurjahan, Pari Shiddho, Paijam, Basmoti, Govindavogh, Katarivogh, Nagirshail and Chinigura. We analyzed Moisture, Ash, Dry Matter, Crude Fibre(CF), Crude Protein(CP),Water soluble protein, Fat, Total Carbohydrate, Metabolizable Energy (ME),Total sugar, Reducing sugar, non-reducing sugar, and minerals when the rice varieties are in polished form and obtained comparative data on their chemical composition and nutritive values. The results revealed the presence of nutrient constituent among the twelve varieties comprising Moisture(10.21±0.07to13.22±0.08%), Ash(0.30±0.02 to 0.57±0.02%), Dry Matter(86.78±0.08 to 89.78±0.07%), Crude Fibre(0.15±0.02 to 0.63±0.02%), Crude Protein(6.31±0.01 to 8.31±0.01%), Water soluble protein(0.13±0.02 to 0.25±0.02%),Fat(0.09±0.01 to 2.90±0.02%), Total Carbohydrate (76.33±0.13 to 81.87±0.05%), Metabolizable Energy (2834.31 to 3017.27 Kcal/Kg), Total sugar(0.06±0.01 to 0.40±0.01%), Reducing sugar(0.01±0.01 to 0.09±0.02%), Non-reducing sugar(0.05±0.01 to 0.36±0.01%) and minerals such as Sodium (69.07±0.13 to 118.87±0.39 mg%), Potassium(0.38±0.02 to 3.41±0.47mg%), Calcium (1.1±0.1 to 1.85±0.03mg%), Magnesium (0.13±0.04 to 0.61±0.01mg%), Iron (0.0003±0.0005 to 0.0005±0.0002mg%), Phosphorus (0.52±0.03 to 2.33±0.03mg%) respectively.